Intermittent Auscultation in Low-Risk Labor. Issue 1 (January 2015) - Wisner, Kirsten
<x xml:space="preserve">Abstract</x> Our new columnist on hot topics in maternity nursing provides information on how to use intermittent auscultation (IA) and encourages you to consider asking for an order for IA, if one does not exist, when caring for women at low risk for complications during labor.